Molecular Characterization of Newly Emerging Foot-and-Mouth Disease Virus Serotype SAT 2 of Lib-12 Lineage Isolated from Egypt - Ayah M. Hassan; Fouad S. El-mayet; Ayman S. El-Habbaa; Momtaz A. Shahein; Mohamed E. El Zowalaty; Naglaa M. Hagag; Saad S.A. Sharawi (Virus Research, 2022)
An outbreak of foot-and-mouth disease virus (FMDV) serotype SAT 2 occurred in Egypt in 2018, which affected cattle and water buffalo. Previous phylogenetic studies on FMDV circulating in Egypt have mainly focused on genomic regions encoding structural proteins which determine FMDV serotype. So far, none of these studies have analyzed the open reading frame (ORF) sequence of Egyptian SAT 2/Lib-12 lineage. The present study aimed to analyze and identify the ORF genome sequence of Lib-12 lineage which belongs to FMDV serotype SAT 2 topotype VII in Egypt. The protocol workflow was optimized and tested using a representative field isolate of FMDV/SAT 2/Lib-12 from a bovine tongue sample collected in 2018 from Ismailia governorate (SAT2/EGY/Ismailia/2018). The protocol was based on reverse transcription polymerase chain reaction with multiple overlapping primers, amplicons sequencing, and assembly to complete the ORF consensus sequence. Alignments of the sequence fragments formed consensus genome sequence of 7219 nucleotides in length. The complete nucleotide sequence of the Egyptian isolate was related to Ethiopian, Nigerian, and Ghanaian strains, with identity not exceeding 95%. The divergence in the genetic identity of the Egyptian SAT 2/Lib-12 lineage from other Egyptian strains and Libyan isolates was 7%, and this may be attributed to the absence of the Lib-12 lineage ORF sequence from Egypt and Libya in the database. The present study significantly advances knowledge of the molecular analysis of FMDV SAT 2 and the design of vaccine selection for FMDV SAT 2 in Egypt. The study protocol could be applied to other FMDV serotypes.